2006
DOI: 10.1519/17204.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maximal Repetition Performance and Muscle Fiber Type as Estimated by Noninvasive Technique in the Quadriceps of Untrained Women

Abstract: The purpose of this investigation was to establish a relationship between the number of repetitions an individual can complete at a predetermined load and their percentage of type II muscle fibers in their quadriceps. Subjects included 22 untrained women between the ages of 18 and 35. Day 1 consisted of noninvasive anthropologic testing, 1 repetition maximum (1RM) testing, and recording repetition performance at 70% 1RM. Day 2 consisted of isokinetic dynamometry to determine muscle fiber composition. Results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 0 publications
1
27
2
4
Order By: Relevance
“…It was recently reported that type I muscle fiber percentage, as estimated by an indirect method, is moderately (r = 0.48) related to the number of repetitions performed at 70% 1RM (6), which is in contrast to the results of the current study. It should be noted that in this previous study, the subjects were women and the performance was determined on a leg extension machine.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that type I muscle fiber percentage, as estimated by an indirect method, is moderately (r = 0.48) related to the number of repetitions performed at 70% 1RM (6), which is in contrast to the results of the current study. It should be noted that in this previous study, the subjects were women and the performance was determined on a leg extension machine.…”
Section: Discussioncontrasting
confidence: 99%
“…Type I fibers have mainly endurance characteristics, while type II muscle fibers have speed and power characteristics (25). Previous studies have suggested that the variability in the number of repetitions that can be performed at a certain percentage of 1RM is influenced by the fiber type composition of the protagonist muscles (6,18). However, in these studies, fiber type composition was only indirectly estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, importante observar que, na segunda etapa, o número de Rms variou entre 7 e 15 Rms entre os sujeitos, sendo este valor similar a outros estudos. Douris (2006) encontram valores que variaram entre 7 a 14 Rms no exercício extensão de joelhos com 70% de 1RM e, embora os autores tenham encontrado uma baixa correlação (r = -0,48; p = 0,04) entre o número de Rms e o tipo de fibra, os mesmos justificam que este fator possa determinar a variabilidade entre os sujeitos, ou seja, sujeitos com maior percentual de fibras do tipo I conseguiriam realizar maior quantidade de Rms, fator este que também poderia auxiliar no entendimento de nossos achados.…”
Section: Discussionunclassified
“…No teste de Rms, utilizando uma carga correspondente a 70% do teste de 1Rm, foi contabilizado o número máximo de repetições realizadas de forma tecnicamente correta (DOURIS, 2006). A velocidade de realização do movimento de flexão foi monitorada de forma visual, sendo indicada a utilização de uma velocidade moderada (≈ 1,5 segundos cada fase -concêntrica e excêntrica).…”
Section: Testes De 1rm E Rmsunclassified
“…We might also consider muscle fiber type (Douris et al 2006), motor unit recruitment and firing patterns (Sale 1987;Westing et al 1991), mechanical efficiency (Nelson et al 2011), and limb length (Miller et al 1993), which can all affect maximal and sustained force production. This means that the knowledge of a person's 1RM for a given muscular load does not provide any accurate basis for prediction of how many repetitions that person can perform at any given %1RM, let alone could it be generalised across other exercises or groups of individuals.…”
Section: Repetitionsmentioning
confidence: 99%